Clinical Guidelines in old age psychiatry - Hughes, Julian C.; Lilford, Philippa, 1989- (Martin Dunitz, 2021)
"Chapter 1 Epidemiology and mental health in old age Philippa Lilford and Julian Hughes Introduction Epidemiology is the study of disease and its determinants in populations. Epidemiological studies investigate what the pattern of diseases are and why they develop in particular populations.[1] Epidemiology is important in improving our understanding of what causes disease. Similarly, understanding epidemiology and how to interpret observational data is crucial to avoid inaccurate causal inferences. Unfortunately, critically evaluating all of the data on mental health problems in old age was outside the scope of this chapter, but we try to highlight some important limitations and gaps in the literature. There are exciting developments in epidemiology that will guide our knowledge about the determinants of psychiatric disease. For example, genomic-wide association studies (GWAS) are increasing our understanding of genetic associations with psychiatric diseases. In Alzheimer's disease (AD), epidemiology has revealed genetic susceptibilities and identified modifiable environmental risk factors, as well as leading to improved diagnostic criteria through the use of biomarkers (see Chapter 10). It has been estimated that modifying risk factors could 'delay or prevent a third of dementia cases',[2] which has enormous implications for the information that clinicians give to their patients, as well as for public health policies"--
To Scan or Not to Scan : Neuroimaging in Mild Cognitive Impairment and Dementia / Victoria Sullivan, Biswadeep Majumdar, Anna Richman, Sobhan Vinjamuri -- Supporting Self-Management in Early Dementia : A Contribution Towards 'Living Well'? / Jo Cheffey, Laura Hill & Glenn Roberts -- What Can Person-Centred Care in Dementia Learn From the Recovery Movement? / Laura Hill, Glenn Roberts, Rachel Perkins -- Psychosocial Interventions in Dementia / Andrew Kiridoshi -- Palliative Care in Dementia : Issues and Evidence / Julian C. Hughes, David Jolley, Alice Jordan, Elizabeth L. Sampson -- Review of Treatment for Late-Life Depression / Katherine Hay, Will Stageman and Charlotte L. Allan -- Reducing the Healthcare Burden of Delirium : The Challenge of Developing More Cognitive-Friendly Services / David J. Meagher, Henry O'Connell, Walter Cullen, Dimitrios Adamis -- Controlling the Confusion : Using Barrier Analysis in the Care Home Sector / Robert Colgate, Alison Turner and Danika Rafferty -- Mental Health Laws from all UK Jurisdictions / Carole Burrell and Charlotte Emmett -- Deprivation of Liberty : Where Are We Now? / Nick Brindle and Christian Walsh -- Residence Capacity : Its Nature and Assessment / Julian C. Hughes, Marie Poole, Stephen J. Louw, Helen Greener and Charlotte Emmett -- Understanding the Person with Dementia : A Clinico-Philosophical Case Discussion / Julian C. Hughes and Aileen Beatty.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Mental Disorders; Alzheimer Disease; Aged; United Kingdom